2008
DOI: 10.4269/ajtmh.2008.78.53
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Human Infection during the 2006 West Nile Virus Outbreak in Davis, a Residential Community in Northern California

Abstract: We collected a total of 15,329 mosquitoes during weekly sampling in Davis, CA, from April through mid-October 2006 at 21 trap sites uniformly spaced 1.5 km apart over an area of approximately 26 km(2). Of these mosquitoes, 1,355 pools of Culex spp. were tested by multiplex reverse transcriptase-polymerase chain reaction, of which 16 pools (1.2%) were positive for West Nile virus (WNV). A degree-day model with a developmental threshold of 14.3 degrees C accurately predicted episodic WNV transmission after three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
6
33
0
Order By: Relevance
“…pipiens are important local WNV vectors (Bolling et al 2007, Gujral et al 2007), which agrees with other studies in the western U.S. (e.g., Reisen et al 2004Reisen et al , 2008Reisen et al , 2009Bell et al 2005;DiMenna et al 2006DiMenna et al , 2007Nielsen et al 2008;Kent et al 2009). The study by Bolling et al (2007) also revealed that the highly abundant human-biter Aedes vexans occasionally is infected with WNV in the Front Range.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…pipiens are important local WNV vectors (Bolling et al 2007, Gujral et al 2007), which agrees with other studies in the western U.S. (e.g., Reisen et al 2004Reisen et al , 2008Reisen et al , 2009Bell et al 2005;DiMenna et al 2006DiMenna et al , 2007Nielsen et al 2008;Kent et al 2009). The study by Bolling et al (2007) also revealed that the highly abundant human-biter Aedes vexans occasionally is infected with WNV in the Front Range.…”
Section: Introductionsupporting
confidence: 90%
“…tarsalis females recorded by us for the plains in 2007 agrees with another study from Weld County in 2007 that also reported high WNV infection rates in Cx. tarsalis (Kent et al 2009 (Nielsen et al 2008). Notably, we did not record any WNV infection in Culex mosquitoes in foothills-montane areas above 1,550 m.…”
Section: Wnv Infection and Vector Index For Culex Femalesmentioning
confidence: 59%
“…Around Davis, California, warm nightly temperatures and positive WNV Cx. pipiens mosquito pools indicated high risk for human WNV incidence (Nielsen et al, 2008). In the Chicago, Illinois area cumulative high temperature differences were a key factor for distinguishing years with higher mosquito infection and higher human illness rates (Ruiz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, there have been numerous national (Landesman et al, 2007;Soverow et al, 2009), state/regional (Day and Shaman, 2008;DeGroote et al, 2008;Wimeberly et al, 2008;Liu et al, 2009), and local Nielsen et al, 2008;Ghosh and Guha, 2010) studies that have investigated or discussed the relationships between WNV infections and at least one landscape, demographic or climatic-related variable. However, to date there have been a lack of studies comprehensively examining regional patterns of WNV occurrence in relation to a range of landscape, demographic and climatically related variables based on ranges of WNV mosquito vector species in the coterminous USA.…”
Section: Introductionmentioning
confidence: 99%
“…tarsalis, respectively (8)(9)(10). To reduce WNV transmission and human exposure to mosquitoes in 2005, the Sacramento-Yolo Mosquito and Vector Control District (SYMVCD) implemented a battery of control practices from their Integrated Pest Management plan (11), an ecosystem-based strategy focused on long-term control of mosquito populations (D. Brown, SYMVCD, pers.…”
Section: W Est Nile Virus (Wnv; Genusmentioning
confidence: 99%